Implementasi Teknik Hibrida Enkripsi Aes Dan Steganografi Multi-Platform Pada Aplikasi Berbasis Web 'Steganoid' - Farid Kurniawan; Abdul Muzakky; Nuafal Aziz Mulyono; Ahmat Fahri Matondang (JIKUM: Jurnal Ilmu Komputer, 2026)
In the era of massive digital information exchange, data security has evolved from mere encryption to the need for confidentiality regarding the existence of the data itself. This research report presents an in-depth analysis, design, and evaluation of SteganoID, a web-based steganography application developed to fulfill the requirements of the Cryptography and Steganography course at Universitas Malikussaleh (UNIMAL). The application integrates the Advanced Encryption Standard (AES) cryptographic algorithm with Least Significant Bit (LSB) steganography techniques and file structure modifications for image, audio, and PDF document media. This study explores the effectiveness of a hybrid approach in securing the text message "UNIMAL HEBAT" within the xrank.pdf file, as demonstrated in system testing. By leveraging client-side processing capabilities through modern JavaScript and HTML5 APIs, SteganoID offers a portable security solution without requiring software installation, mitigating privacy risks associated with server-side processing. This report comprehensively outlines the theoretical foundation, system architecture, interface implementation, and analysis of robustness against steganalysis attacks.